2018
DOI: 10.1007/s42250-018-00036-9
|View full text |Cite
|
Sign up to set email alerts
|

Furfuryl Alcohol a Versatile, Eco-Sustainable Compound in Perspective

Abstract: Renewable agricultural biomass derived chemicals, their modifications and uses have seen multiplicity in numerous applications and important processes with major impacts on the pursuit for eco-sustainability. Such applications range include the energy sector, chemistry, pharmacy, the textile industry, paints and coatings, plastic industry, to name but a few. This field of lignocellulosic derived chemicals interconnects several scientific disciplines ranging from agriculture, biochemistry, engineering, environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 105 publications
(131 reference statements)
0
72
0
1
Order By: Relevance
“…Including recent progress in the characterization of its combustion properties, production processes, theoretical kinetic explorations and fundamental combustion properties. The theoretical efforts are focused on the mechanistic pathways for furan decomposition and oxidation, as well as the development of detailed chemical kinetic models 2018 [39] Furthermore, it is well-known that, the field of furan chemistry, both theoretically and in the applied segment is very huge, and no single work can exhaust its many applications that range, from the chemical, to electrical and electronics, pharmacy, biomedical, medicine, the textile, paints and coatings, plastics industry, to name but a few [2,[49][50][51]. Interestingly, according to the density functional theory (DFT) calculations, it has been shown that the heterocyclic furan ring is particularly prone to ring opening, preferably via the C-O bond [52], which can be harnessed for generating tailored and tuneable products, thereby, broadening the application portfolio of furanic systems whether in bio-refineries and/or application materials as has been exemplified in the work of Fan et al [53], when they demonstrated a self-crosslinking elastomeric thermoset via furan ring-opening mechanism.…”
Section: Historical Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Including recent progress in the characterization of its combustion properties, production processes, theoretical kinetic explorations and fundamental combustion properties. The theoretical efforts are focused on the mechanistic pathways for furan decomposition and oxidation, as well as the development of detailed chemical kinetic models 2018 [39] Furthermore, it is well-known that, the field of furan chemistry, both theoretically and in the applied segment is very huge, and no single work can exhaust its many applications that range, from the chemical, to electrical and electronics, pharmacy, biomedical, medicine, the textile, paints and coatings, plastics industry, to name but a few [2,[49][50][51]. Interestingly, according to the density functional theory (DFT) calculations, it has been shown that the heterocyclic furan ring is particularly prone to ring opening, preferably via the C-O bond [52], which can be harnessed for generating tailored and tuneable products, thereby, broadening the application portfolio of furanic systems whether in bio-refineries and/or application materials as has been exemplified in the work of Fan et al [53], when they demonstrated a self-crosslinking elastomeric thermoset via furan ring-opening mechanism.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Inedible lignocellulosic biomass is well-known to be a favourable feedstock and its momentous change in the pursuit for green and sustainable chemistry is of great importance in the modern day well-deserved environmental concerns. Their renewability, enormous availability, sustainability, capacity and potential for transmutation into various kinds of chemical compounds, far exceeding those derived from petroleum-based feedstock, has been demonstrated over the years [1,2]. With global challenges on energy security, non-sustainable petroleum resources, volatile oil prices, global warming, and the attendant environmental challenges, associated with fossil hydrocarbons, studies have demonstrated that, with concerted efforts by governments, industries and policymakers at all levels, in a synergised collaboration with other key players, promoting the use of inedible agricultural residues, such as: oat hulls, rice husks, sugarcane bagasse, woody material wastes, etc., as alternative sources for biobased chemical feedstock, comes with sundry associated benefits, which include, but is not limited to: (a) increased absorption of atmospheric CO 2 as more wood and other lignocellulosic biomass will be cultivated/or grown to feed the process, thereby mitigating global warming, (b) the reduction in the dependence on fossil-derived fuels and chemicals, (c) increased opportunities in the local agricultural sector, which directly impacts on food security and job creation, (d) economic transformation, to mention but a few [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations